Overview of EV Charging Smart Control Architecture-Recent Developments - Faujdar B.; Pandey R.K. (My University, 2025)
Electric Vehicle Charging Infrastructure is an essential component in deployment of Electric Vehicles at large scale in the world. The Smart Control Architecture is the backbone for facilitating the EV charging/Battery swapping in real time environment. The massive usage of EV in transportation is only feasible once the charging infrastructure is structured/facilitated intelligently to provide seamless charging in the respective region with upcoming EV penetration. The massive integration of EVs charging point/bay in Distribution System may also result in an unacceptable performance at given point of time in case the power infeed to the charging infrastructure is not properly regulated depending on the vehicle penetration. The paper firstly reviews the concept for Smart Control Architecture for upcoming EV Charging points/bay in each distribution/sub-transmission system and also highlights the requirements of intelligent power control to the respective charging infrastructure for quality and quick charging in order to ensure regulated power control for distribution system sustainability and reliability. © 2023 IEEE.